BUiD Doctoral Research Conference 2022 Multidisciplinary Studies - Al Marri, Khalid; Mir, Farzana; David, Solomon; Aljuboori, Aos (Lecture Notes in Civil Engineering,, 2023)
This open access book presents selected contributions on a wide range of scientific and technological areas originating from the BUiD Doctoral Research Conference (BDRC 2022). It discusses the following topics: project management, macroeconomic factors, Fourth Industrial Revolution, agility, multiculturalism, diversity, inclusion, leadership, language, discourse analysis, curriculum, critical thinking, programming, online learning, and natural ventilation. The contributions reflect the multifaceted nature of the research in three academic disciplines, i.e., humanities, formal science, and applied science. This publication shares with its readers genuine research studies and reflections from practitioners on the current practice and understanding in the three academic disciplines. The significant findings of these studies have considerable educational, industrial, and economic implications.